2015
DOI: 10.1038/ncomms7317
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical bias introduced during RNA synthesis modulates the activity of phosphorothioate siRNAs

Abstract: An established means of improving the pharmacokinetics properties of oligoribonucleotides (ORNs) is to exchange their phosphodiester linkages for phosphorothioates (PSs). However, this strategy has not been pursued for small interfering RNAs (siRNAs), possibly because of sporadic reports that PS siRNAs show reduced inhibitory activity. The PS group is chiral at phosphorous (Rp/Sp centres), and conventional solid-phase synthesis of PS ORNs produces a population of diastereoisomers. Here we show that the choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…One underappreciated outcome of PS insertions is the introduction of stereoisomers relative to the non‐stereomeric PO backbone (Figure ). Standard oligonucleotide synthesis lacks stereocontrol, but the issue was ignored primarily due to the success of PS‐containing oligonucleotides in the clinic and lack of practical stereopure PS synthetic methodology. Stereopure PScontaining oligonucleotides became a reality with the development of oxazaphospholidine methods .…”
Section: Figurementioning
confidence: 99%
“…One underappreciated outcome of PS insertions is the introduction of stereoisomers relative to the non‐stereomeric PO backbone (Figure ). Standard oligonucleotide synthesis lacks stereocontrol, but the issue was ignored primarily due to the success of PS‐containing oligonucleotides in the clinic and lack of practical stereopure PS synthetic methodology. Stereopure PScontaining oligonucleotides became a reality with the development of oxazaphospholidine methods .…”
Section: Figurementioning
confidence: 99%
“…reported that the PS‐siRNAs composed of oligoribonucleotides (ORNs) with a higher fraction of Rp centres showed greater resistance to nucleases in serum and were more effective inhibitors in cells than their Sp counterparts. Introduction of phosphorothioate (PS) modifications in the place of phosphodiester linkages of siRNA exhibited improved potency when tested in HeLa cells by luciferase assay …”
Section: Phosphate Backbone Modificationsmentioning
confidence: 99%
“…: 6655.3; ref. 40). Chemicals for ORN synthesis were from Aldrich and TCI (Sigma-Aldrich Chemie GmbH, D-89555 Steinheim).…”
Section: Synthesis Of Sirna For In Vivo Studiesmentioning
confidence: 99%
“…This previously characterized siRNA (siLin28B-2) was selected for its high knockdown efficiency (40). Transfection of siLin28B-2 reduced Lin28B mRNA and concomitantly increased let-7b expression in DU145 cells ( Supplementary Fig.…”
Section: Targeting Of Lin28 In Prostate Cancer Cells Blocks Csc Self-mentioning
confidence: 99%